Enhancement of laser heating process by laser surface modification on titanium alloy - A. Q., Zaifuddin; F., Zulhilmi; Aiman, Mohd Halil; Quazi, M. M.; M., Ishak (Faculty Mechanical Engineering, UMP, 2021)
Titanium alloys are widely utilized in laser heating applications. However, it has poor optical properties due to low laser energy absorption. Nevertheless, a higher energy absorption can be realized by modifying the surface profile through increasing the surface roughness. In this present work, the laser surface modification (LSM) process was carried out to increase the roughness on surface of Ti6Al4V titanium alloy. Subsequently, the surface characterization and surface roughness were analysed by using the 3D optical microscope. The effect of laser power on the increment of surface roughness was investigated. It was revealed that an increase in laser power during LSM process could increase the surface roughness. The result shows that, the surface roughness of titanium alloy increased 27 times when modified with the highest laser power (27W) compared to the gritted surface. Furthermore, the modified surface by LSM will be heated using laser radiation in order to analyse the effect of surface roughness towards laser heating temperature. Depending on the value of the power during laser heating, the maximum temperature measured could be increased 27% corresponding to a gritted flat reference surface.